THE EFFECT OF INDIVIDUAL SELECTION FOR GENETIC DIVERSITY OF Acacia mangium SEEDLING SEED ORCHARD USING AFLP MARKERS - A. Y.P.B.C. Widyatmoko; S. Shiraishi; A. Nirsatmanto; H. Kawazaki (Indonesian Journal of Forestry Research, 2006)
Establishment of seed orchard is aimed at producing good quality seeds which is an important activity for breeding program. Seed orchard is also a base population, thus its genetic diversity is depending on its design and composition (provenance, family and individual tree). Selection of an individual tree in seed orchard is needed for the enhancement of  retaining good-character trees. However, selection of individual tree can change the genetic diversity of seed orchard, and the degrees to which the genetic diversity will change depend on the used selection methods. In order to investigate the effects of selection methods, 4 simulations of selection methods based on height, diameter and stem performance of individual trees were used. The differences among the 4 methods were the ranking of individual trees those selected, and families and provenances those have been represented. Seedling seed orchard of Acacia mangium in Wonogiri, Central Java was used as materials.Analysis of genetic diversity was carried out using AFLP markers. Nine primer combinations were used to produce 1025 AFLP banding patterns. Among those banding patterns, only 109 were polymorphic markers. No significant effect of individual tree selection was revealed in this study. Even though the selection was done intensively, only 7.1% of genetic diversity was reduced. In other words, the selection activity did not reduce the genetic diversity of seed orchard significantly. The result is important for developing future tree improvement of A. mangium, including development of hybrid between A. mangium and A. auriculiformis.